The Role of Membrane, Feed Characteristic and Process Parameters on RED Power Generation - Heru Susanto; Meike Fitrianingtyas; I Nyoman Widiasa; Titik Istirokhatun; Yunita Fahni; Assalaam Umar Abdurahman (International Journal of Renewable Energy Development, 2023)
Reverse electrodialysis (RED) is a renewable energy-generating SGE technique using energy from salinity gradients. This research investigates the effect of membrane and feed characteristics on reverse electrodialysis (RED) power generation. Some investigations on the process parameters effect for the complement of the main study were also conducted. The generated power of RED was measured using power density analysis. The experiments were performed using artificial seawater varied from 0 to 1 g/L NaCl for diluted salt water and from 0 to 40 g/L NaCl for concentrated salt water. In a study of ions type, NaCl non-pa is used to represent monovalent ions, and MgSO4 represents divalent ions. The results showed that the highest voltage generation is 2.004 volts by 14 cells number of the RED membrane utilizing a RED self-made laboratory scale. The power density was enhanced by raising the flow rate (0.10 L/min), concentration difference (40 g/L), and the presence of electrode rinse solution. Further, the ion type (monovalent, divalent, and multivalent) influenced the resulting RED power density, where the divalent ion (MgSO4) 's power density was greater than that of the monovalent ion (NaCl). The resistance and selectivity of the membrane were the major keys for the power generation of RED